The road to excellence in women`s football: a retrospective cohort study over the last 30 years with Swiss national players - Charbonnet, B.; Schmid, M. J.; Örencik, M.; van Niekerk, E.; Conzelmann, A. (Science and Medicine in Football, 2024)
Objectives: This study examines the training (age at club entry, hours in club practice, free play, other sports) and environmental characteristics (popularity, media coverage, school and parental support) influencing the development of female Swiss national team players in elite football over a three-decade period. Methods: A retrospective questionnaire was completed by 84 participants, who were divided into three cohorts based on their first game with the Swiss national team (C1 = until 2000, n = 24; C2 = 2001-2010, n = 29; C3 = 2011-2022, n = 31). ANOVAs were employed to compare the cohorts regarding training and environmental variables. Results: The findings demonstrate better perceived environmental conditions, stagnating volume of free play and other sports in childhood, decreasing age at club entry, and increasing club practice and total training volume across cohorts. Conclusion: Practical implications highlight talent development avenues in unstructured settings during free time and in the micro-structure of club practice.